PERTUMBUHAN DAN PERKEMBANGAN PESERTA DIDIK TINGKAT SMP DI CABANG OLAHRAGA BADMINTON - Ekowati; Bekti Gunawan (EDU RESEARCH, 2024)
The growth and development of students in junior high school (SMP) is a crucial period for the formation of character and optimal physical skills. Badminton, as a sport requiring agility, strength, and endurance, is an ideal choice for enhancing the physical, mental, and social development of adolescents. This article aims to analyze how badminton contributes to improving these aspects in junior high school students. Through a qualitative approach and observation of training activities and competitions, this article reveals that badminton enhances physical endurance, coordination skills, and social interaction among students. Moreover, psychological aspects such as self-confidence and stress management also improve with their involvement in this sport.